Factors associated with the intention to vaccinate and price sensitivity to the human papillomavirus (HPV) vaccine among Chinese male medical college students: a cross-sectional survey - Yuan Li; Hiromi Kawasaki; Zhengai Cui; Sae Nakaoka (PeerJ, 2025)
Background College students, particularly males, face a high risk of the human papillomavirus (HPV) infection, yet vaccination rates remain low in China. This study aims to explore the willingness to receive HPV vaccine among Chinese male medical college students based on health literacy (HL) theory and price sensitivity. Methods A cross-sectional survey was conducted from June 16 to July 16, 2024, to assess socioeconomic status and HL among college students at Guangdong Medical University. The survey was distributed via WeChat using convenience sampling through the Chinese online survey platform “Wenjuanxing” (http://www.wjx.cn). A Van Westendorp price sensitivity meter (PSM) was used to determine male medical college students’ price sensitivity to HPV vaccines. Results Among 1,631 valid participants, 59.4% (n = 969) expressed willingness to receive HPV vaccination. The key influencing factors included graduate status (OR: 1.82; 95% CI [1.00–3.32]; p = 0.049), family history of cancer (OR: 1.29; 95% CI [1.01–1.66]; p = 0.041), moderate daily exercise (OR: 53; 95% CI [1.21–192]; p < 0.001), peers’ HPV vaccination status (OR: 1.42; 95% CI [1.15–1.75]; p < 0.001), and HL levels (OR: 1.03; 95% CI [1.01–1.05]; p = 0.002). The Van Westendorp PSM analysis demonstrated high price sensitivity: the market price of the quadrivalent vaccine aligned closely with the lowest price point for male medical college students, whereas the nine-valent vaccine’s market price exceeded the acceptable price range. Conclusions HL levels directly increased HPV vaccination intentions, and PSM analysis revealed the nine-valent vaccine’s market price exceeded the acceptable price range, contrasting with the affordability-aligned quadrivalent vaccine. Interventions should prioritize HL programs and cost-reduction strategies (e.g., subsidies for the nine-valent vaccine), while addressing nonprice barriers (including family history of cancer, moderate daily exercise and peer influence networks), particularly for the quadrivalent vaccine.